Phylogenetic analysis of dermatophytes isolated from small domestic animals - A. M. Smagulova; E. V. Kukhar; T. I. Glotova; A. G. Glotov (Ветеринария сегодня)
Dermatophytoses are diseases of skin and its accessory structures that are widely spread worldwide. They are most commonly caused by fungi of the genera Micro- sporum and Trichophyton. The identification of the agent’s species has a great epidemiological significance and is essential for effective therapy. The aim of the study is the identification and phylogenetic analysis of dermatophytes isolated from dogs and cats in the Republic of Kazakhstan and the Russian Federation by means of molecular techniques. The fungal isolate species were confirmed by sequencing using two rDNA internal transcribed spacer (ITS) primer pairs, and this allowed for their deposition to the GenBank database. Based on the sequencing results, Microsporum canis (12 strains) and Trichophyton benhamiae (2 strains) were identified. The nucleotide sequences were analysed, and phylogenetic trees were constructed, taking into account the results of the dermatophyte identification using two primer pairs. The constructed phylogenetic trees reflecting the relationships of dermatophytes showed that, irrespective of the primer pairs used, the Microsporum and Trichophyton pathogens are in all cases reliably assigned to different clades. The analysis of ITS4F/ITS5R sequence fragment structures enabled the establish- ment of genetic relatedness between the Trichophyton benhamiae strains first isolated from cats in Russia and the Russian strain recovered from a guinea pig. The comparative analysis of the genomes of the Microsporum and Trichophyton fungi and reference strains revealed a relatively low level of intraspecies polymor- phism and point mutations of the sequences. The data analysis demonstrated a high percentage of nucleotide sequence homology, and this allows using the primers for PCR tests intended for dermatophytosis diagnosis in cats and dogs.